A resource for the simultaneous high-resolution mapping of multiple quantitative trait loci in rats: The NIH heterogeneous stock - Johannesson, Martina; Lopez-Aumatell, Regina; Stridh, Pernilla; Diez, Margarita; Tuncel, Jonatan; Blázquez, Gloria; Martinez-Membrives, Esther; Cañete, Toni; Vicens-Costa, Elia; Graham, Delyth; Copley, Richard R.; Hernandez-Pliego, Polinka; et al.

(untitled) (Genome Research, 2009)
The laboratory rat (Rattus norvegicus) is a key tool for the study of medicine and pharmacology for human health. A large database of phenotypes for integrated fields such as cardiovascular, neuroscience, and exercise physiology exists in the literature. However, the molecular characterization of the genetic loci that give rise to variation in these traits has proven to be difficult. Here we show how one obstacle to progress, the fine-mapping of quantitative trait loci (QTL), can be overcome by using an outbred population of rats. By use of a genetically heterogeneous stock of rats, we map a locus contributing to variation in a fear-related measure (two-way active avoidance in the shuttle box) to a region on chromosome 5 containing nine genes. By establishing a protocol measuring multiple phenotypes including immunology, neuroinflammation, and hematology, as well as cardiovascular, metabolic, and behavioral traits, we establish the rat HS as a new resource for the fine-mapping of QTLs contributing to variation in complex traits of biomedical relevance.